Crown tissue proportions and enamel thickness distribution in early Pleistocene Homo antecessor maxillary premolars (Atapuerca, Spain). Issue 2 (24th December 2022) - Martín‐Francés, Laura; Martinón‐Torres, María; de Pinillos, Marina Martínez; Xing, Song; Soligo, Christophe; García‐Campos, Cecilia; Modesto‐Mata, Mario; de Castro, José María Bermúdez
Abstract: Objectives: Both morphometric and proteomic studies have revealed the close relationship of Homo antecessor with Neanderthals and H. sapiens . Considering this relationship, we aim to characterize the Early Pleistocene Atapuerca‐Gran Dolina (TD6) maxillary premolars to test if their pattern of enamel thickness is shared with Neanderthals or H. sapiens . Materials and Methods: We employed microcomputed tomography to estimate 2D and 3D tissue proportions in seven H. antecessor maxillary premolars, belonging to two individuals: H1 and H3, and compared them to a sample of extinct and extant Homo populations of African, Asian and European origin ( n  = 52). Results: Our results reveal a different pattern of enamel thickness between the Atapuerca‐Gran Dolina two individuals. While TD6‐H1 possesses thin‐enameled crowns, with a clear affinity with Neanderthals, TD6‐H3 exhibits the thick pattern, a trait shared with the majority of fossil hominins and H. sapiens . Discussion: This work provides new data on upper premolar enamel thickness in H. antecessor . By documenting both a thin and a thick pattern of enamel thickness in the TD6 sample, we warn about the taxonomic utility of this feature in the characterization of isolated remains. We suggest that the thin enamel condition would have emerged during the Early Pleistocene and it became the most frequent and typical condition in Neanderthals. Possible causes for the pattern observed in TD6 include sexual dimorphism or presence of two populations in the sample; however, population variability is the most plausible explanation with a character expression intermediate between those of Neanderthals and other members of the genus Homo . This interpretation is compatible with the phylogenetic position of H. antecessor close to the ancestor of Neanderthals and H. sapiens .